Preparation and Studies of Cerium Dioxide(CeO2) Nanoparticles by Microwave-assisted Solution Method - K. Balasubramanian3, E. Kumar1, P. Selvarajan2,ï€ª and (Recent Research in Science and Technology, 2010)
In this paper, synthesis and characterization of ceriumÂ  dioxide (CeO2) or ceria nanoparticles are presented. Nanoparticles of cerium dioxide were synthesized by solution method using a microwave oven. The precursor used to prepare the nanoparticles of CeO2 was ammonium ceric nitrate. The precursor was dissolved in de-ionized water and pH value of the solution was adjusted to be at 12 using sodium hydroxide and the solution was kept on the microwave oven to synthesize the ceria nanoparticles.Â  Synthesized yellow precipitate was filtered, washed and annealed and the sample was subjected to various characterization techniques like XRD, FTIR, SEM, TG/DTA, UV-visible absorption studies, conductivity studies and the results are presented and discussed.